1990
DOI: 10.1073/pnas.87.9.3255
|View full text |Cite
|
Sign up to set email alerts
|

A frequent tyrosinase gene mutation in classic, tyrosinase-negative (type IA) oculocutaneous albinism.

Abstract: We have identified a tyrosinase gene mutation in several patients with classic, tyrosinase-negative (type IA) oculocutaneous albinism. This mutation, which results in a proline --leucine substitution at codon 81 of the tyrosinase polypeptide (EC 1.14.18.1), was observed in 20% (6 of 30) of oculocutaneous albinism alleles from independent probands, but it was not observed in any normal individuals. This mutation thus appears to be a frequent cause of tyrosinasenegative oculocutaneous albinism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…The identity of Tyrp1 was clarified soon afterward, with the cloning of authentic human and mouse tyrosinase (TYR, Tyr) sequences (29,30). Completion of these sequences was followed rapidly by the identification of tyrosinase mutations in human oculocutaneous albinism type 1 (31,32) and the common albino mouse (33). This was another landmark, the identification of the first color mutation in human and mouse.…”
Section: Melanosomal Componentsmentioning
confidence: 99%
“…The identity of Tyrp1 was clarified soon afterward, with the cloning of authentic human and mouse tyrosinase (TYR, Tyr) sequences (29,30). Completion of these sequences was followed rapidly by the identification of tyrosinase mutations in human oculocutaneous albinism type 1 (31,32) and the common albino mouse (33). This was another landmark, the identification of the first color mutation in human and mouse.…”
Section: Melanosomal Componentsmentioning
confidence: 99%
“…The availability of tyrosinase cDNA enabled us and others to identify mutations in human and murine tyrosinase-negative albinos (10)(11)(12)(13)(14). In this report, we show a mutation in the tyrosinase gene of a tyrosinase-negative albino patient that resulted in an inactive enzyme with an altered carboxyl terminus.…”
mentioning
confidence: 75%
“…In that case, it was not demonstrated that the albino melanocytes produced the predicted truncated tyrosinase. Another tyrosinase gene mutation was reported by Giebel et al (13) in 6 out of 30 unrelated tyrosinase-negative albinos, where a change from C to T (CCT --CTT) at codon 81 (codon 63 of the Pmel34A sequence, Fig. 3) would result in a substitution of leucine for proline.…”
Section: Discussionmentioning
confidence: 99%
“…As expected from PAX3's interactions, mutations in SOX10 can cause a WS2 phenotype as well; WS2E (#611584) was identified in 2009 in a boy who had the WS2 phenotype plus neurological manifestations, including Tyrosinase crucially catalyses the conversion of tyrosine to DOPAquinone, the precursor for both eumelanin and pheomelanin. Complete loss of tyrosinase activity causes oculocutaneous albinism type 1 (OCA1A, #203100), an autosomal recessive disorder in which pigment is completely absent from the integument and the eyes [23]. A further defining characteristic is misrouting of the optic nerves, which manifests outwardly in the eyes moving to and fro rhythmically, a movement known as nystagmus.…”
Section: Introductionmentioning
confidence: 99%
“…In people with reduced tyrosinase activity, logically, some pigment will still be formed and they consequently have the so-called "yellow" type of albinism (OCA1B, #606952) [24].…”
Section: Introductionmentioning
confidence: 99%